Marking Technique to Isolate Boundary Router and Attacker. - Vijairahavan, Vaarun; Shah, Darshak; Galgali, Pallavi; Shah, Amit; Shah, Nikhil; Srinivasan, Venkatesh; Bhatia, Lokesh (Computer (00189162), 2007)
The article discusses a new method by which denial-of-service (DoS) attacks can be traced back to the attacker if the attacker is using slave computers to conceal its origin. DoS attackers flood the target network and its computers with heavy traffic, which degrades or denies service to legitimate users. Tracing attacks back to the attacker will stop the attacks, however if the attacker is filtering attacks through slave computers, then this process can be difficult. The method devised by the authors is called speedy IP traceback which attempts to pinpoint the boundary router. Advantages and disadvantages of this method are discussed. Several charts and diagrams are included in the text.